2012
DOI: 10.1177/1363459312438565
|View full text |Cite
|
Sign up to set email alerts
|

‘I deal with the small things’: The doctor–patient relationship and professional identity in GPs’ stories of cancer care

Abstract: An important part of GPs' work consists of attending to the everyday and existential conditions of human being. In these life world aspects, biomedicine is often not the relevant theory to guide the GP; nevertheless they are a part of GPs' professional domain. In cancer care, previous studies have shown that GPs with a biomedical perspective on medicine could feel subordinate to specialists, and that doctors with a curative focus could see disease progression as a personal failure. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…) and their interactions with care‐givers, stressing the social processes that shape decision‐making, disclosure and interpretation of results (Gross , Johansen et al . , , Sarradon‐Eck et al . ; Stacey et al .…”
Section: Living With and Beyond Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…) and their interactions with care‐givers, stressing the social processes that shape decision‐making, disclosure and interpretation of results (Gross , Johansen et al . , , Sarradon‐Eck et al . ; Stacey et al .…”
Section: Living With and Beyond Cancermentioning
confidence: 99%
“…Articles on patient-caregiver interactions and service uptake were primarily focused on understanding and improving or supporting patients' understandings of risk and responsibility (Heyman et al 2012, Mendick et al 2010, Sinding et al 2010 and their interactions with care-givers, stressing the social processes that shape decision-making, disclosure and interpretation of results (Gross 2012, Johansen et al 2012, Sarradon-Eck et al 2012Stacey et al 2009). These included decision-making beyond treatment, fertility preservation (Quinn et al 2008) and participation in early-stage trials (Jansen 2014).…”
Section: Identity and Subjectivitymentioning
confidence: 99%
“…Four articles suggested that wisdom emerges within practitioners' practice experience as cancer care providers (Cueva, 2011; Johansen et al, 2012; Jordens & Little, 2004; O'Callaghan, 2005). Wisdom is often termed in this context as “practical wisdom” or “practice wisdom.” Jordens and Little (2004) utilized narrative inquiry and genre theory to study ethical reasoning from interviews with clinicians treating colorectal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Johansen and colleagues (2012) offer some perspective on “practical wisdom” and its tensions in the clinical practices of general practitioners (GPs) in oncology care. They used a thematic narrative approach in a study with 14 GPs in Norway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation